Transculturalism and Business in the BRIC States: A Handbook - Brühwiler, Claudia Franziska (EBL-Schweitzer, 2015)
Cover; Contents; List of Figures; List of Tables; List of Text Boxes; List of QR-Codes; List of Abbreviations; Acknowledgments; About the Editors; About the Contributors; Introduction; PART I: Theoretical Framework; 1 Hall, Hofstede, Huntington, Trompenaars, GLOBE: Common Foundations, Common Flaws; 2 Cultural Negotiations in the BRIC TransAreas- New Dynamic Visualizing Models of Culture Contact Situations; 3 Transcultural Studies in the BRIC States: Recent Developments; PART II Areas-BRIC by BRIC; 4 BRIC Foundations: New Kids on the Block and the Implications for Transcultural Communication